2001
DOI: 10.1088/0953-4075/34/3/323
|View full text |Cite
|
Sign up to set email alerts
|

Experimental MoIIoscillator strengths

Abstract: Experimental branching fractions (BFs) of Mo II, ranging in wavelength from 1970 to 4370 Å, have been measured from intensity calibrated spectra recorded with the Lund UV Fourier transform spectrometer (FTS). Radiative lifetimes for 10 levels have been measured using the method of laser-induced fluorescence (LIF). Combining BFs with new as well as previously measured lifetimes, 16 in total, oscillator strengths of 91 lines were derived. Seven transitions are resonance lines involving the ground state. The BF r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 15 publications
7
50
1
Order By: Relevance
“…The results fall in the range from 2.2 to 7.5 ns. One can see that the lifetime of the 48 022.82 cm −1 level reported by Hannaford and Lowe [7] and Sikström et al [8] with the LIF method agrees well with our result. But for [13].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The results fall in the range from 2.2 to 7.5 ns. One can see that the lifetime of the 48 022.82 cm −1 level reported by Hannaford and Lowe [7] and Sikström et al [8] with the LIF method agrees well with our result. But for [13].…”
Section: Resultssupporting
confidence: 93%
“…The lifetimes of the levels at 48 022.82 and 60 992.76 cm −1 , which were investigated previously by Hannaford and Lowe [7], Sikström et al [8] and by Lundberg et al [10], respectively, were also measured in the present paper for comparison. Corresponding theoretical lifetime values were also calculated using the multiconfigurational HFR method taking core-polarization effects into account, and they are in good agreement with the experimental results having in mind the complexity of the calculations in such heavy atomic systems.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Within this project the term analyses of Y ii (Nilsson et al 1991), Mo ii (Nilsson & Pickering 2003), Ru ii (Karlsson et al 2002), Pd ii (Litzén et al 2001) and Ag ii (Kalus et al 2002) have been published, and analyses of Zr ii and Rh ii are in progress. Oscillator strengths have been measured in Zr ii (Sikström et al 1999;Ljung et al 2006), Mo ii (Sikström et al 2001), Ru ii (Johansson et al 1994) and Pd ii (Lundberg et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Later on, Sikström et al (2001) reported experimental radiative lifetimes for 10 levels by the same method. With the HFR approach including core-polarization effects, theoretical lifetimes for 37 levels of Mo II and the oscillator strengths of the depopulating transitions were calculated by Quinet (2002).…”
Section: Introductionmentioning
confidence: 99%